2016
DOI: 10.1513/annalsats.201507-435oc
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation in Detection of Granulomas in the Mediastinal Lymph Nodes

Abstract: In this single-center study, there was a high concordance between ROSE and the final cytological diagnosis for mediastinal lymph nodes containing granulomas that were sampled by EBUS-TBNA. ROSE may serve to reduce procedure time, enhance sample triaging, and obviate the need for further invasive testing. The only variable associated with increased concordance was the experience of the operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…ROSE was concordant with final pathology in only 71% of cases. This supports the perception that many providers use ROSE as an assessment of tissue adequacy rather than as a diagnostic tool, although other studies have found higher ROSE concordance rates 38 40 and many factors may affect ROSE usage and efficacy. Use of ROSE was not a significant predictor of increased diagnostic yield for peripheral pulmonary lesions in NAVIGATE (78.6% with ROSE vs. 75.8% without ROSE).…”
Section: Discussionsupporting
confidence: 74%
“…ROSE was concordant with final pathology in only 71% of cases. This supports the perception that many providers use ROSE as an assessment of tissue adequacy rather than as a diagnostic tool, although other studies have found higher ROSE concordance rates 38 40 and many factors may affect ROSE usage and efficacy. Use of ROSE was not a significant predictor of increased diagnostic yield for peripheral pulmonary lesions in NAVIGATE (78.6% with ROSE vs. 75.8% without ROSE).…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have assessed the value of ROSE in patients with suspected sarcoidosis undergoing EBUS‐TBNA . Plit et al performed EBUS‐TBNA with ROSE followed by TBB and bronchial biopsies in a prospective cohort of 60 patients with suspected sarcoidosis.…”
Section: Why Has Ebus Become Invaluable For the Diagnosis Of Sarcoidomentioning
confidence: 99%
“…Besides ROSE, whose role has been discussed in detail in section EBUS‐TBNA material can undergo rapid on‐site cytological evaluation , a few technical aspects specific to EBUS‐TBNA in sarcoidosis have been studied and deserve mentioning.…”
Section: Introduction Route and Technical Aspectsmentioning
confidence: 99%
“…This study shows that not only malignant diseases, ROSE technology can also help hilar mediastinal benign lesions for on-site rapid diagnosis. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%